Prozeßkontrolle und -steuerung beim Laserstrahlschweißen mit den Methoden der nichtlinearen Dynamik - Geisel, Mark (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2002)
A new process control for laser welding applications is introduced. This method, known as resonant stimulation, effects the laser welding process by small laser power modulations which result in an increased weld seam quality. A systematic approach for the determination of suitable control parameter is explained on the basis of the transfer function of the laser welding proces